In Vivo Hemodynamic Changes of Vortex Vein Varix on Real-Time Video Angiography. Issue 2 (February 2017) - Kang, Tony D.; Douglass, Alexzandra M.; Ferenczy, Sandor R.; Say, Emil Anthony T.; Shields, Carol L.
Abstract : Supplemental Digital Content is Available in the Text.